Minangkabau Local Wisdom Education: Strengthening Students' Moral Courage, Altruism, and Social Solidarity - Sabar Aulia Rahman; Gusmira Wita; Muhammad Agus Hardiansyah; Irhas Fansuri Mursal (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2026)
The moral degradation of adolescents in the era of globalization necessitates the reinforcement of identity through education rooted in local wisdom. This study aims to examine the influence of Minangkabau Culture-Based Character Education (PKBAM) on students' moral courage, altruism, and social solidarity. Using a quantitative survey design, data were collected from 431 junior high school students in Bukittinggi via proportionate stratified random sampling. The data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that PKBAM has a positive and significant impact on all three dimensions of moral character, with the strongest effect on social solidarity. These findings support the notion that incorporating local cultural values into education plays a crucial role in shaping civic character, in alignment with the goals of civic education. This study contributes to the advancement of civic education practices that are contextually relevant and grounded in a sociocultural framework. It is recommended that policymakers strengthen local content curricula as tools for fostering a national character that is both adaptive and deeply rooted in the nation's cultural heritage.